The Propaganda of Intolerance Act on Instagram: Multimodal Discourse Analysis on #patungbundamaria - Khairul Syafuddin; Jamalullail; Mohammad Nuruzzaman (Mediator: Jurnal Komunikasi, 2023)
The case of covering the Virgin Mary statue using a tarpaulin is one of the viral cases related to religious issues. The case involved an Islamic mass organization in Kulon Progo Yogyakarta and the owner of the Sasana Adhi Rasa prayer house, ST Yacobus. Some of the posts about the case use the hashtag #patungbundamaria. Hashtags, which intended originally to promote sculpture products, suddenly used to increase the reach of spreading issues. This is as an effort to carry out propaganda that has the potential to bring up a discourse of intolerance. This study aims to determine the form of multimodal discourse from the case of the closing of the Bunda Maria statue in Kulon Progo, as well as the propaganda formed. This research method uses a qualitative approach with a constructivist paradigm. The analysis technique is through multimodal discourse analysis. Researchers look at the use of multimodal text to build propaganda messages with the addition of hashtag modes. The results of this study indicate that the emergence of the issue of the Virgin Mary statue by using hashtags begins in the form of gray propaganda. This is because the data to raise this issue is still not valid due to pursuing posting speed. However, from the process of developing issues on social media, the message shift to white propaganda. In addition, netizens on Instagram have a concern in rejecting intolerance. They seek to suppress the emergence of intolerant discourse by providing comments that encourage tolerance between religious communities.